The Endocrine Society's 92nd Annual Meeting, June 19–22, 2010 - San Diego 2010
DOI: 10.1210/endo-meetings.2010.part2.p10.p2-491
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Acinar-Specific Overexpression of Reg2 Gene Offered No Protection Against Either Experimental Diabetes or Pancreatitis in Mice.

Abstract: Reg proteins are normally expressed in pancreatic acinar cells, and the level of several of these proteins was significantly induced upon damage to the endocrine or exocrine pancreas. It has been established that Reg1 and pancreatic islet neogenesis-associated protein [INGAP, Reg3␦] promote the growth or regeneration of the endocrine islet cells. Recent reports suggest that Reg2 is an autoantigen normally expressed in islet ␤-cells. Reg2 overexpression in vitro offered protection to insulinoma cells. Overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…In our early research, overexpression of Reg2 ameliorated mitochondrial and endoplasmic reticulum (ER)‐stress‐induced cell death in MIN6 cells . In vivo, however, acinar‐specific overexpression of Reg2 provided no protection in STZ‐induced diabetic mice, leading to doubt that insufficient protein synthesis and secretion may be the key . Recently, we found that islet‐specific Reg2 knockout in aged and obese mice caused the diabetic conditions to deteriorate, suggesting that Reg2 expression is required for pancreatic islet compensation .…”
Section: Introductionmentioning
confidence: 99%
“…In our early research, overexpression of Reg2 ameliorated mitochondrial and endoplasmic reticulum (ER)‐stress‐induced cell death in MIN6 cells . In vivo, however, acinar‐specific overexpression of Reg2 provided no protection in STZ‐induced diabetic mice, leading to doubt that insufficient protein synthesis and secretion may be the key . Recently, we found that islet‐specific Reg2 knockout in aged and obese mice caused the diabetic conditions to deteriorate, suggesting that Reg2 expression is required for pancreatic islet compensation .…”
Section: Introductionmentioning
confidence: 99%